2017
DOI: 10.1080/16506073.2017.1332095
|View full text |Cite
|
Sign up to set email alerts
|

Is cognitive behavioural therapy effective in reducing suicidal ideation and behaviour when delivered face-to-face or via e-health? A systematic review and meta-analysis

Abstract: Cognitive Behavioural Therapy (CBT) is a widely used psychotherapeutic intervention for suicide prevention despite its efficacy for suicide prevention in adults remaining ambiguous. Reluctance or inability to access face-to-face help suggests that e-health delivery may be a valuable resource for suicidal people. The aim of this study was to systematically review and conduct meta-analysis on research assessing the efficacy of CBT delivered via face-to-face and e-health for suicidal ideation and behaviour. A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 58 publications
(57 reference statements)
2
34
1
1
Order By: Relevance
“…Among psychotherapies, individual cognitive behavioural therapy has been reported to significantly reduce suicidal thoughts and behaviour compared to treatment as usual 162,176 . In a recent meta-analysis 177 , dialectical behaviour therapy was found to be effective in reducing suicidal behaviour and re-attempt, especially in females with borderline personality disorder.…”
Section: Treatment Of Mental Disordersmentioning
confidence: 99%
“…Among psychotherapies, individual cognitive behavioural therapy has been reported to significantly reduce suicidal thoughts and behaviour compared to treatment as usual 162,176 . In a recent meta-analysis 177 , dialectical behaviour therapy was found to be effective in reducing suicidal behaviour and re-attempt, especially in females with borderline personality disorder.…”
Section: Treatment Of Mental Disordersmentioning
confidence: 99%
“…While this might be the case, comprehensive evidence for the effectiveness of technology-enhanced approaches in reducing suicide risk is still lacking. While Internet-based cognitive behavioural therapy (CBT) seems to be as effective as traditional face-to-face CBT in reducing psychiatric distress in general [42], in contrast to traditional CBT, Internet-based CBT was not found effective in reducing suicidality [43]. A systematic review by Witt and colleagues reported some evidence for the effectiveness of online and phone-based applications for the self-management of suicidal ideation and self-harm in reducing suicidality [44].…”
Section: Technology-enhanced Interventionsmentioning
confidence: 99%
“…Some reviews suggest that they might be effective in reducing suicidal ideation [ 27 , 28 , 29 , 30 , 31 ], with effect sizes in meta-analyses of randomized controlled trials ranging from Hedges’ g = −0.23, 95% CI −0.35 to −0.11 [ 27 ] to g = −0.29, 95% CI −0.40 to −0.19 [ 28 ] at post-intervention. Other reviews, however, did not find significant positive effects on suicidal ideation [ 32 , 33 , 34 ]. Low treatment adherence further limits the confidence in the benefits of this new treatment approach for clinical practice [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%